Positive electrode material, preparation method, battery and electric device
Patent Information
- Application Number
- CN202511254456.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请所要解决的技术问题是提供一种正极材料、制备方法、电池和用电设备,以解决相关技术中当电池工作电压提升至高电压时,三元正极材料结构不稳定问题加剧,导致其循环变差、充气严重的问题
[0043]本申请实施例所提供的正极材料,在三元正极材料的内核中引入了氟离子,由于氟的高电负性特性,其与过渡金属离子形成的金属-氟键的键能高于金属-氧键,从而抑制了过渡金属离子在电化学循环过程中的迁移和溶出,提升了三元正极材料内核结构的稳定性;同时,还在三元正极材料内核表面构建氧离子导体包覆层,氧离子导体包覆层能够容纳内核中因高电压脱锂而释放的氧,避免内核与电解液发生氧化副反应,进而缓解三元正极材料在高压条件下的氧流失和产气问题;进一步地,具有氟元素的三元正极材料与氧离子导体包覆层两者的协同作用提升了三元正极材料在高电压下的结构稳定性和循环稳定性。
Smart Images

Figure CN123017906A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a cathode material, a preparation method, a battery, and an electrical device. Background Technology
[0002] Lithium-ion batteries are energy storage devices that rely on the repeated insertion and extraction of lithium ions between positive and negative electrodes to achieve charging and discharging. They have advantages such as high energy density, long cycle life, and no memory effect. The positive electrode material, as the storage carrier of lithium ions and the center of the redox reaction, directly determines the battery's energy density, cycle life, and safety. Currently, mainstream positive electrode materials include lithium cobalt oxide, lithium iron phosphate, and ternary cathode materials, among which ternary cathode materials are the preferred choice for lithium batteries due to their high energy density.
[0003] Ternary cathode materials achieve high voltage platforms and high capacities by adjusting the proportions of nickel, cobalt, manganese, or aluminum. However, when the battery operating voltage is increased to high voltages, the structural instability of ternary cathode materials worsens, leading to poorer cycle life and severe gas accumulation. Summary of the Invention
[0004] The technical problem to be solved by this application is to provide a cathode material, a preparation method, a battery, and an electrical device to solve the problem in the related technology that when the battery operating voltage is increased to a high voltage, the structural instability of the ternary cathode material is aggravated, resulting in poor cycle performance and severe gas accumulation.
[0005] To solve the above problems, this application provides the following technical solution:
[0006] This application proposes a cathode material, comprising:
[0007] The core comprises a ternary cathode material containing fluorine.
[0008] A shell layer disposed on the surface of the core, the shell layer comprising an oxygen ion conductor.
[0009] Furthermore, the oxygen ion conductor is a multivalent metal-based transition metal oxide, wherein the multivalent metal includes at least one of La, Zr, Ce, and Bi.
[0010] Furthermore, the chemical formula of the oxygen ion conductor is:
[0011] La2M2O9, where M represents at least one of W, V, Nb, Ta, and Mo.
[0012] Furthermore, the chemical formula of the kernel is:
[0013] LiNi a Co b Mn c O2-0.5d F d , where a+b+c=1, 0.5<a<0.8, 0<d≤0.02.
[0014] Furthermore, in the positive electrode material, the mass ratio of the oxygen ion conductor to fluorine is (0.25~1):1.
[0015] Furthermore, in the positive electrode material, the content of the oxygen ion conductor is 1000-3000 ppm.
[0016] This application also proposes a method for preparing a cathode material, the method comprising:
[0017] A ternary cathode material precursor containing fluorine was prepared by mixing a nickel source, a cobalt source, a manganese source, a fluorine source, a precipitant solution, and a complexing agent solution.
[0018] The ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor are mixed to prepare a ternary cathode material precursor containing fluorine coated with the oxygen ion conductor precursor.
[0019] The fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor is mixed with lithium salt and sintered to obtain the fluorine-containing ternary cathode material coated with the oxygen ion conductor.
[0020] Furthermore, the molar ratio of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source is a:b:c, where a+b+c=1 and 0.5<a<0.8.
[0021] Furthermore, the sum of the amounts of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source, and the amount of fluorine in the fluorine source, is in the ratio of 1:(0.0008 to 0.0012).
[0022] Furthermore, in the mixture composed of the ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor, the content of the oxygen ion conductor precursor is 1000-3000 ppm.
[0023] And / or, the oxygen ion conductor precursor comprises a multivalent metal salt and a transition metal salt, wherein the molar ratio of the multivalent metal element in the multivalent metal salt to the transition metal element in the transition metal salt is 1:(1.01~1.02);
[0024] And / or, the mass ratio of the oxygen ion conductor precursor to the fluorine element in the fluorine source is (0.25~1):1.
[0025] Furthermore, the multivalent metal salt is at least one of lanthanum salt, zirconium salt, cerium salt, and bismuth salt.
[0026] Furthermore, the transition metal element is at least one selected from W, V, Nb, Ta, and Mo.
[0027] Furthermore, when the transition metal element is W, the transition metal salt is at least one of tungsten chloride, ammonium tungstate, and sodium tungstate;
[0028] When the transition metal element is V, the transition metal salt is at least one of ammonium metavanadate and vanadium chloride;
[0029] When the transition metal element is Nb, the transition metal salt is at least one of niobium oxalate, niobium chloride, and niobium sulfate;
[0030] When the transition metal element is Ta, the transition metal salt is at least one of tantalum oxalate, tantalum chloride, and tantalum sulfate;
[0031] When the transition metal element is Mo, the transition metal salt is at least one of ammonium molybdate, sodium molybdate, and potassium molybdate.
[0032] Furthermore, the molar ratio of the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor to the lithium element in the lithium salt is 1:(0.50~0.52).
[0033] Furthermore, a ternary cathode material precursor containing fluorine is prepared by mixing a nickel source, a cobalt source, a manganese source, a fluorine source, a precipitant solution, and a complexing agent solution, further comprising:
[0034] Nickel source, cobalt source, manganese source and fluorine source are mixed evenly in solvent, precipitant and complexing agent are added to make the pH of the solution 11-12, and the reaction is carried out by stirring in a water bath at 60-70℃ for 1-2 hours.
[0035] After aging in a water bath at 60℃~70℃ for 12~13h, the precipitate is obtained by vacuum filtration. The precipitate is then washed and dried to obtain the ternary cathode material precursor containing fluorine.
[0036] Further, the ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor are mixed to prepare a ternary cathode material precursor containing fluorine coated with the oxygen ion conductor precursor, which further includes:
[0037] The fluorine-containing ternary cathode material precursor and the oxygen ion conductor precursor are mixed evenly in a solvent and subjected to a hydrothermal reaction at 100–200°C for 8–12 h to obtain a fluorine-containing ternary cathode material precursor coated with an oxygen ion conductor precursor.
[0038] Further, the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor is mixed with a lithium salt and sintered to obtain an oxygen ion conductor-coated fluorine-containing ternary cathode material, which further comprises:
[0039] The fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor and lithium salt are ball-milled and mixed, and then sintered under a protective atmosphere to obtain the fluorine-containing ternary cathode material coated with the oxygen ion conductor. The sintering temperature is 650-750℃ and the sintering time is 9-11h.
[0040] This application also proposes a battery, including a positive electrode and a negative electrode; the positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive electrode material as described above.
[0041] This application also proposes an electrical device, including the battery described above, wherein the battery serves as the power supply for the electrical device.
[0042] Compared with related technologies, the embodiments of this application have the following advantages:
[0043] The cathode material provided in this application introduces fluoride ions into the core of the ternary cathode material. Due to the high electronegativity of fluorine, the bond energy of the metal-fluorine bond formed with transition metal ions is higher than that of the metal-oxygen bond, thereby inhibiting the migration and dissolution of transition metal ions during electrochemical cycling and improving the stability of the core structure of the ternary cathode material. At the same time, an oxygen ion conductor coating layer is constructed on the surface of the ternary cathode material core. The oxygen ion conductor coating layer can accommodate the oxygen released in the core due to high-voltage lithium delithiation, avoiding oxidation side reactions between the core and the electrolyte, thereby alleviating the oxygen loss and gas generation problems of the ternary cathode material under high-voltage conditions. Furthermore, the synergistic effect of the fluorine-containing ternary cathode material and the oxygen ion conductor coating layer improves the structural stability and cycle stability of the ternary cathode material under high voltage.
[0044] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description
[0045] Figure 1 This is a flowchart of the steps in a method for preparing a cathode material provided in an embodiment of this application. Detailed Implementation
[0046] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to specific embodiments.
[0047] In related technologies, ternary cathode materials, as the core cathode system of current power batteries, achieve higher specific capacity while maintaining a high operating voltage platform by adjusting the ratio of nickel, cobalt, and manganese. However, with the increase of charging voltage, the structural instability of ternary cathode materials becomes increasingly prominent. When the charging voltage exceeds 4.3V, nickel ions in the ternary cathode material are oxidized to higher valence Ni. 4+ This unstable high-valence state triggers the irreversible release of lattice oxygen, causing the ternary cathode material to gradually transform from an ordered layered structure to a disordered spinel phase or even an insulating rock salt phase. This irreversible transformation of the crystal structure not only causes rapid capacity decay but also leads to the dissolution of transition metal ions. These dissolved transition metal ions migrate to the negative electrode surface, damaging the stability of the SEI film (Solid Electrolyte Interphase) and further accelerating the deterioration of battery performance. Furthermore, under high-voltage conditions, the active oxygen remaining on the surface of the ternary cathode material undergoes a violent oxidation reaction with the electrolyte, producing a large amount of gaseous products, leading to increased internal battery pressure and posing serious safety hazards.
[0048] Furthermore, from a microscopic perspective, the structural degradation of ternary cathode materials under high voltage is a complex process involving multiple coupled factors. Specifically, as lithium ions are continuously extracted, the material lattice undergoes anisotropic volume shrinkage. This uneven stress distribution generates microcracks within the secondary particles, exposing more fresh surfaces to contact the electrolyte. These newly exposed surfaces further exacerbate the oxidative decomposition of the electrolyte, forming a thicker interfacial impedance layer that hinders lithium ion transport. Simultaneously, high-valence transition metal ions catalyze the electrolyte decomposition reaction, producing more gaseous byproducts and acidic substances. These byproducts, in turn, corrode the cathode material surface, creating a vicious cycle.
[0049] To address the aforementioned problems, this application provides a cathode material comprising a core and a shell. The core comprises a ternary cathode material containing fluorine, and a shell layer is disposed on the surface of the core, comprising an oxygen ion conductor. In this application embodiment, fluorine ions are introduced into the core of the ternary cathode material because fluorine has high electronegativity, and the bond energy of the metal-fluorine bond formed with transition metal ions is higher than that of the metal-oxygen bond. This suppresses the migration and dissolution of transition metal ions during electrochemical cycling, thereby improving the stability of the core structure of the ternary cathode material. Simultaneously, in this application embodiment, an oxygen ion conductor coating layer is constructed on the surface of the core of the ternary cathode material. This oxygen ion conductor coating layer can accommodate the oxygen released from the core structure due to high-voltage lithium delithiation, preventing oxidation side reactions between the core and the electrolyte, thus alleviating the oxygen loss and gas generation problems of the ternary cathode material under high-voltage conditions. Therefore, this application improves the structural stability and cycle stability of the ternary cathode material under high voltage through the synergistic effect of the fluorine-containing ternary cathode material and the oxygen ion conductor coating layer.
[0050] Optionally, the oxygen ion conductor is a multivalent metal-based transition metal oxide, where the multivalent metal is at least one of La, Zr, Ce, and Bi. The oxygen ion conductor precursor may include, but is not limited to, multivalent metal salts and transition metal salts. The multivalent metal salt is at least one of lanthanum, zirconium, cerium, and bismuth salts. This is because the ionic radii of elements such as lanthanum, zirconium, cerium, and bismuth have good coordination compatibility with transition metals, ensuring lattice matching between the oxygen ion conductor coating layer and the ternary cathode substrate, thereby reducing interfacial stress.
[0051] Furthermore, the oxygen ion conductor is a lanthanum-based transition metal oxide with the chemical formula La₂M₂O₉, where M represents at least one of W, V, Nb, Ta, and Mo. When the polyvalent metal salt is a lanthanum salt, the lanthanum salt is at least one of lanthanum chloride and lanthanum nitrate. These soluble polyvalent metal salts have moderate solubility, enabling atomically homogeneous mixing. The transition metal element is at least one of W, V, Nb, Ta, and Mo. The high oxidation state of these transition metal ions can balance the charge imbalance caused by oxygen vacancies and can also form a rigid polyhedral framework with the polyvalent metal to suppress lattice shrinkage during sintering.
[0052] In this embodiment, the chemical formula of the core is: LiNi a Co b Mn c O 2-0.5d F d , where a+b+c=1, 0.5<a<0.8, 0<d≤0.02.
[0053] It should be noted that excessive substitution of oxygen anions with fluoride ions will introduce too many anion vacancies, causing local collapse of the layered structure and reducing the lithium ion diffusion rate. Therefore, in the cathode material of this application embodiment, the mass ratio of oxygen ion conductor to fluorine element is (0.25~1):1.
[0054] It should be noted that an excessively thick oxygen ion conductor coating layer will hinder the diffusion of lithium ions from the electrolyte to the bulk phase of the cathode material, increasing the interfacial impedance. However, if the oxygen ion conductor content is insufficient, a continuous and uniform oxygen ion conductor coating layer cannot be formed, resulting in some of the ternary cathode material surface directly contacting the electrolyte, causing transition metal dissolution and oxygen loss. Therefore, in the cathode material of this application embodiment, the oxygen ion conductor coating layer content is 1000-3000 ppm.
[0055] It is understood that the battery prepared based on the positive electrode material provided in the embodiments of this application includes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material provided in the embodiments of this application.
[0056] Reference Figure 1 This application also provides a method for preparing a positive electrode material, including steps S101 to S103.
[0057] Step S101: Mix the nickel source, cobalt source, manganese source, fluorine source, precipitant solution and complexing agent solution to prepare a ternary cathode material precursor containing fluorine.
[0058] Step S102: Mix the ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor to prepare a ternary cathode material precursor containing fluorine coated with the oxygen ion conductor precursor.
[0059] Step S103: Mix the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor and the lithium salt, and sinter to obtain the fluorine-containing ternary cathode material coated with the oxygen ion conductor.
[0060] In step S101, firstly, nickel source, cobalt source and manganese source are mixed and dissolved according to the molar ratio of ternary metal elements Ni, Co and Mn of 6:1:3 to obtain ternary metal solution; fluorine source is dissolved according to the molar ratio of the sum of the ternary metal elements to the molar ratio of fluorine in fluorine source of 1:(0.0008~0.0012) to obtain fluorine-containing solution; precipitant is dissolved to obtain precipitant solution; complexing agent is diluted to obtain complexing agent solution.
[0061] It should be noted that in preparing the ternary cathode material precursor, a nickel, cobalt, and manganese molar ratio of 6:1:3 was used. This ratio retains the excellent specific capacity provided by the high nickel content, maintains electronic conductivity through an appropriate amount of cobalt, and suppresses phase transitions during charge and discharge processes through the stabilizing effect of manganese. The fluorine doping amount is controlled at 0.08–0.12% of the total ternary metal content, which is the optimal range for balancing the modification effect and side effects. Too little doping cannot effectively stabilize the crystal lattice, while too much may generate impurity phases.
[0062] The nickel source is at least one of nickel nitrate, nickel sulfate, and nickel chloride; the cobalt source is at least one of cobalt nitrate, cobalt sulfate, and cobalt chloride; and the manganese source is at least one of manganese nitrate, manganese sulfate, and manganese chloride. These soluble salts all have moderate solubility, enabling atomic-level homogeneous mixing. Among them, nickel nitrate / cobalt / manganese is the preferred choice due to its high solubility and low residual anion properties, while the sulfate system is more suitable for large-scale industrial production.
[0063] The fluorine source is at least one of ammonium fluoride, potassium fluoride, sodium fluoride, and magnesium fluoride. These fluoride salts all have moderate solubility in aqueous solutions, enabling controlled release of fluoride ions and avoiding uneven doping caused by excessively high local concentrations.
[0064] The precipitant is at least one of ammonium carbonate, ammonium bicarbonate, sodium carbonate, and sodium hydroxide. The selection of the precipitant takes into account both nucleation kinetics and product morphology control. Ammonium carbonate / ammonium bicarbonate can achieve mild co-precipitation under neutral to weakly alkaline conditions (pH = 8-9), avoiding component segregation caused by local supersaturation, while sodium hydroxide is suitable for processes requiring rapid precipitation.
[0065] The complexing agent is at least one of ammonia, ammonium bicarbonate, and citric acid. Ammonia, in particular, can form [Ni(NH3)6]... 2+ The iso-complexes slow down the precipitation rate to obtain a precursor with good sphericity and can also adjust the pH of the solution; ammonium bicarbonate provides additional CO3. 2- The source promotes the formation of carbonate precursors; the three carboxyl groups and one hydroxyl group in the citric acid molecule can simultaneously react with Ni. 2+ Co 2+ Mn 2+ Multiple metal ions form a stable multidentate coordination structure. This strong complexation can significantly slow down the precipitation rate of metal ions, making the coprecipitation reaction more uniform and controllable.
[0066] Then, the fluorine-containing solution and the ternary metal solution are mixed evenly to obtain a fluorine-containing ternary metal solution. A precipitant solution and a complexing agent solution are then added, and the pH of the mixed solution formed by the fluorine-containing solution, the ternary metal solution, the precipitant solution and the complexing agent solution is adjusted to 11-12.
[0067] Then, the mixture is stirred for 1-2 hours at a water bath temperature of 60-70℃ and a rotation speed of 300-500 rpm. It is then aged for 12-13 hours at 60-70℃ and a rotation speed of 300-500 rpm to allow the precursor particles to further undergo crystal phase reorganization, surface passivation, or component homogenization.
[0068] Finally, a vacuum filtration device was used to separate the solid and liquid components of the aged slurry. A Buchner funnel and microporous membrane were used for filtration under negative pressure to obtain a wet precipitate of the fluorine-containing ternary cathode material precursor. To thoroughly remove residual free ions and organic impurities from the precipitate, a staged washing process was employed: first, the precipitate was washed three times with deionized water under ultrasonic assistance, each time using five times the volume of the precipitate; then, it was washed twice with anhydrous ethanol to reduce subsequent drying energy consumption. The washed fluorine-containing ternary cathode material precursor was then placed in a vacuum drying oven and dried at 80℃ and -0.1MPa for 12 hours, turning it over every 2 hours to ensure uniform heating. The final product was a loosely powdered fluorine-containing ternary cathode material precursor with a water content of <1wt%.
[0069] It should be noted that in step S101, by adding a fluorine-containing solution and a precipitant solution to the ternary metal solution, fluorine ions are uniformly doped into the crystal structure of the ternary cathode material precursor during the co-precipitation process. This in-situ doping process ensures the uniform distribution of fluorine in the crystal structure of the ternary cathode material precursor, avoiding the local enrichment of fluorine ions that may occur during subsequent processing. Furthermore, the introduction of fluorine ions partially replaces the positions of hydroxide ions. During the subsequent sintering process, the pre-doped fluorine can effectively suppress the migration of transition metal ions during high-temperature sintering and reduce cation mixing. On the other hand, the presence of fluorine can also regulate the surface chemical properties of the ternary cathode material precursor, with F- replacing part of the surface O. 2- Subsequently, it will reduce the surface free energy of the ternary cathode material precursor, causing its surface to change from hydrophilic to hydrophobic, promoting the uniform spreading of the oxygen ion conductor precursor solution on the surface of the ternary cathode material precursor, and providing favorable conditions for the uniform growth of the subsequent oxygen ion conductor coating layer.
[0070] In step S102, a ternary cathode material precursor containing fluorine and an oxygen ion conductor precursor are prepared according to the following ratio: In the mixture composed of the ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor, the content of the oxygen ion conductor precursor is 1000–3000 ppm. This concentration range ensures the formation of a continuous and dense oxygen ion conductor coating layer while avoiding excessive coating that would lead to a decrease in the proportion of active material and obstruction of lithium ion diffusion. The oxygen ion conductor precursor includes a multivalent metal salt and a transition metal salt. The molar ratio of the multivalent metal element in the multivalent metal salt to the transition metal element in the transition metal salt is 1:(1.01–1.02). A trace excess of transition metal compensates for the volatilization loss during the high-temperature sintering process, ensuring the stoichiometric accuracy of the final product. Meanwhile, since excessive fluorine doping can destroy the density of the coating layer, the fluorine content in the ternary cathode material precursor containing fluorine should be considered when calculating the amount of oxygen ion conductor precursor. In the embodiments of this application, the mass ratio of oxygen ion conductor precursor to fluorine in fluorine source is (0.25~1):1. This ratio can achieve the synergistic effect of fluorine doping and oxygen ion conductor coating. That is, fluorine can stabilize the crystal lattice of the host material and partially integrate into the coating layer to optimize its ionic conductivity, while avoiding excessive fluorine from destroying the density of the coating layer.
[0071] Optionally, the oxygen ion conductor precursor may include, but is not limited to, multivalent metal salts and transition metal salts. The multivalent metal may include at least one of lanthanum, zirconium, cerium, and bismuth salts. This is because the ionic radii of lanthanum, zirconium, cerium, and bismuth have good coordination compatibility with transition metals, ensuring lattice matching between the oxygen ion conductor coating layer and the ternary cathode substrate, thereby reducing interfacial stress. When the multivalent metal salt is a lanthanum salt, the lanthanum salt is at least one of lanthanum chloride and lanthanum nitrate. These soluble multivalent metal salts have moderate solubility, enabling atomically homogeneous mixing.
[0072] The transition metal element is at least one of W, V, Nb, Ta, and Mo. The high oxidation state of these transition metal ions can balance the charge imbalance caused by oxygen vacancies and can also form a rigid polyhedral framework with multivalent metals, inhibiting lattice shrinkage during sintering. When the transition metal element is W, the transition metal salt is at least one of tungsten chloride, ammonium tungstate, and sodium tungstate; when the transition metal element is V, the transition metal salt is at least one of ammonium metavanadate and vanadium chloride; when the transition metal element is Nb, the transition metal salt is at least one of niobium oxalate, niobium chloride, and niobium sulfate; when the transition metal element is Ta, the transition metal salt is at least one of tantalum oxalate, tantalum chloride, and tantalum sulfate; when the transition metal element is Mo, the transition metal salt is at least one of ammonium molybdate, sodium molybdate, and potassium molybdate. The transition metal salts are selected from chlorides, oxalates, sulfates, or tungstates of W, V, Nb, Ta, and Mo, mainly because they can form stable polyacid anions, maintain solubility in an alkaline precipitation environment, and avoid co-precipitation with the host material, thus preventing component segregation. These transition metal salts can all generate the target oxygen ion conductor through solid-state reaction during sintering, and most of the residual anions can volatilize, reducing the introduction of impurities.
[0073] Then, the fluorine-containing ternary cathode material precursor and the oxygen ion conductor precursor prepared in step S101 are mixed evenly in a solvent. During mixing, ultrasonic dispersion can be used for 30-40 minutes to ensure uniform suspension of the material. The material is then transferred to a hydrothermal reactor and reacted at 100-200℃ for 8-12 hours. During the reaction, stirring is maintained at 200-300 rpm to promote uniform coating. After the reaction is completed, a fluorine-containing ternary cathode material precursor coated with an oxygen ion conductor precursor is obtained.
[0074] In step S103, lithium salt is first taken according to the ratio of fluorine-containing ternary cathode material precursor coated with oxygen ion conductor precursor to lithium element in lithium salt with a molar ratio of 1:(0.50~0.52). Lithium salt is preferably at least one of lithium hydroxide, lithium carbonate, and lithium acetate.
[0075] In preparing fluorine-containing ternary cathode materials coated with oxygen ion conductors, controlling the molar ratio of the oxygen ion conductor precursor to the lithium salt within the range of 1:(0.50–0.52) allows for a slight excess of lithium, effectively compensating for lithium volatilization losses during high-temperature sintering. Lithium hydroxide, lithium carbonate, and lithium acetate are preferred as lithium sources primarily because these lithium salts can completely decompose into active lithium oxide within the temperature range of 300–500°C, avoiding impurity residues. Furthermore, the gases produced during decomposition (such as carbon dioxide and water) contribute to the formation of porous structures, enhancing lithium-ion diffusion kinetics.
[0076] Then, the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor prepared in step S102 and the lithium salt are ball-milled together. Zirconia balls are used as the milling medium, with a ball-to-material ratio of 10:1. Wet ball milling is performed in anhydrous ethanol for 4–6 hours to ensure uniform mixing. The mixed powder is then placed in a corundum crucible and heated to 650–750°C under an oxygen or air atmosphere, and held for 9–11 hours to complete the sintering reaction, obtaining the fluorine-containing ternary cathode material coated with the oxygen ion conductor. The oxygen ion conductor is a multivalent metal-based transition metal oxide, and the multivalent metal includes at least one of La, Zr, Ce, and Bi.
[0077] Optionally, the oxygen ion conductor is a lanthanum-based transition metal oxide. The chemical formula of the oxygen ion conductor is La₂M₂O₉, where M represents at least one of W, V, Nb, Ta, and Mo. The chemical formula of the ternary cathode material containing fluorine is LiNi. a Co b Mn c O 2-0.5d F d Where a + b + c = 1, 0.5 < a < 0.8, and 0 < d ≤ 0.02. The chemical formula of the ternary cathode material containing fluorine and coated with an oxygen ion conductor is: LiNi a Co b Mn c O 2-0.5d F d @La2M2O9.
[0078] It should be noted that during the sintering process, when the temperature rises to 300–400℃, the ternary cathode material precursor containing fluorine first undergoes a thermal decomposition reaction, removing structural water and transforming into a transition metal oxide intermediate phase. Simultaneously, fluorine, in the form of fluoride ions, partially replaces lattice oxygen sites, forming strong metal-fluorine bonds in the core lattice of the ternary cathode material precursor. As the temperature continues to rise to 500–600℃, the lithium salt melts and undergoes a solid-state reaction with the transition metal oxide. Meanwhile, the pre-coated oxygen ion conductor precursor undergoes a crystallization transformation at a high temperature of 600–700℃. Multivalent metal ions and transition metal ions combine with lattice oxygen to form a continuous coating layer. During this process, fluorine is partially incorporated into the oxygen ion conductor lattice, preferentially occupying oxygen vacancy sites and thus enhancing the ionic conductivity of the oxygen ion conductor. Because the active oxygen vacancies on the surface of the ternary cathode material precursor particles containing fluorine have strong coordination with polyvalent metal ions and transition metal ions in the early stage of sintering, the oxygen ion conductors tend to grow in a directional manner on the outer surface, forming a dense coating layer, and finally obtaining a cathode material with a core-shell structure.
[0079] The cathode material preparation method provided in this application first involves co-precipitating fluorine into a ternary cathode material precursor to obtain a fluorine-containing ternary cathode material precursor. Then, the fluorine-containing ternary cathode material precursor and an oxygen ion conductor precursor are thoroughly mixed in a solvent system. Through a hydrothermal reaction, the oxygen ion conductor precursor is uniformly distributed on the surface of the fluorine-containing ternary cathode material precursor. Finally, the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor and a lithium salt are sintered at high temperature to generate a core-shell structured fluorine-containing ternary cathode material coated with an oxygen ion conductor. The preparation method of this application combines hydrothermal coating with high-temperature sintering. The hydrothermal reaction ensures that the oxygen ion conductor precursor can be uniformly and tightly attached to the surface of the ternary cathode material precursor containing fluorine, laying a good foundation for the formation of a dense oxygen ion conductor protective layer in the subsequent sintering process. The sintering process, through temperature control and atmosphere adjustment, not only ensures the complete formation of the layered structure of the main material, but also promotes the transformation of the oxygen ion conductor precursor into a highly crystalline oxygen ion conductor.
[0080] This application also provides a battery, which includes a positive electrode and a negative electrode; the positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive electrode material as described above.
[0081] The above-described cell embodiment includes the aforementioned positive electrode active material and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description of the positive electrode material embodiment.
[0082] The aforementioned positive electrode active material layer further includes a conductive agent and a binder; the conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres; the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.
[0083] In the case of a liquid battery, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer can be a negative active material used in batteries. The negative active material can be selected from metallic negative active materials or non-metallic negative active materials. The metallic negative active material can be selected from metal foils or alloy compounds such as sodium, sodium alloys, tin, and antimony. The non-metallic negative active material can be selected from any one or a combination of at least two of hard carbon, soft carbon, graphite, and silicon suboxide.
[0084] The negative electrode sheet also includes conductive agents and binders; the conductive agents include one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene; the binders include sodium carboxymethyl cellulose (CMC) based binders and resin-based binders.
[0085] Optionally, the carboxymethyl cellulose-based adhesive includes one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or the resin-based adhesive includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), and polyacrylonitrile (PAN).
[0086] When the battery is an all-solid-state battery, the negative electrode can be any of the following: graphite-based negative electrode, silicon-based negative electrode, or metal negative electrode.
[0087] The battery provided in this application also includes an electrolyte. The electrolyte acts as a conductor of ions between the positive and negative electrodes, and can be liquid, gel-like, or entirely solid. In some embodiments, the electrolyte is a liquid electrolyte solution comprising an electrolyte salt and a solvent. The electrolyte salt is a lithium salt, and the solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the organic solvent includes ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.
[0088] In some embodiments, the electrolyte is a solid electrolyte, which may be a sulfide solid electrolyte; the sulfide solid electrolyte includes Li 10 GeP2S 12 It is at least one of the following: Thio-LISICON, Li2S-P2S5, and sulfide-germanium ore.
[0089] In the case of a liquid battery provided in this application, the battery also includes a separator.
[0090] In practical applications, when the battery is a liquid battery, the negative electrode, separator and positive electrode can be stacked in sequence and wound to obtain a core. The core is then packaged to obtain a bare cell. After baking, the bare cell is injected with liquid, formed, repackaged and sorted to obtain a liquid battery.
[0091] In the case of an all-solid-state battery, the positive electrode, solid electrolyte, and negative electrode can be stacked in sequence in a solid-state battery mold and then cured to obtain an all-solid-state battery.
[0092] This application also proposes an electrical device, wherein the electrical device includes the battery as described above, and the battery serves as the power supply for the electrical device.
[0093] The above-described electrical equipment embodiments include the aforementioned battery and achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the battery embodiments.
[0094] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0095] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0096] The present application will be described in detail below through embodiments.
[0097] Example 1
[0098] (1) Preparation of ternary cathode material precursor containing fluorine element
[0099] Nickel sulfate, cobalt sulfate, manganese sulfate, and ammonium fluoride were dissolved in a solvent at a molar ratio of 6:1:3:0.01 and mixed thoroughly to obtain a fluorine-containing ternary metal solution. The solvent was a mixture of anhydrous ethanol and deionized water at a volume ratio of 1:1. Sodium carbonate was dissolved in pure water to obtain a precipitant solution. Ammonia water was diluted to obtain a complexing agent solution.
[0100] Then, the precipitant solution and complexing agent solution were added together to the fluorine-containing ternary metal solution. The pH of the mixed solution formed by the fluorine-containing ternary metal solution, precipitant solution and complexing agent solution was adjusted to 12. The mixture was stirred for 1 hour at a water bath temperature of 60°C and a rotation speed of 300 rpm.
[0101] Continue aging at 60℃ and 300rpm for 12 hours;
[0102] Finally, the aged slurry was vacuum filtered to obtain a precipitate. The precipitate was then washed and placed in an oven to dry at 100°C for 12 hours to obtain a ternary cathode material precursor containing fluorine: Ni. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 .
[0103] (2) Preparation of fluorine-containing ternary cathode material precursor coated with oxygen ion conductor precursor
[0104] Lanthanum chloride, niobium chloride, and solvent were added to the fluorine-containing ternary cathode material precursor prepared in step (1) and mixed evenly. A hydrothermal reaction was then carried out at 150°C for 10 hours to obtain a fluorine-containing ternary cathode material precursor Ni coated with an oxygen ion conductor precursor. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 @La2Nb2(OH)9. In the mixture of the ternary cathode material precursor containing fluorine, lanthanum chloride and niobium chloride, the total mass percentage of lanthanum chloride and niobium chloride is 1000 ppm, and the molar ratio of lanthanum chloride to niobium chloride is 1:1.
[0105] (3) Preparation of ternary cathode material with fluorine element coated with oxygen ion conductor.
[0106] A ternary cathode material precursor containing fluorine and coated with an oxygen ion conductor precursor prepared in step (2) at a molar ratio of 1:0.51 was added to a ball mill and mixed at 1000 rpm for 10 min. Then, the mixture was placed in a muffle furnace and heated to 700 °C at 5 °C / min and held for 10 h to obtain an oxygen ion conductor coated with fluorine ternary cathode material LiNi. 0.6 Co 0.1 Mn0.3O 1.995 F 0.01 @La2Nb2O9.
[0107] (4) Preparation of positive electrode sheet
[0108] The fluorine-coated ternary cathode material, conductive carbon black, and binder prepared in step (3) were ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2. The obtained slurry was coated onto the cathode current collector aluminum foil using a 150 μm doctor blade and then dried in a vacuum drying oven at 100 °C for 12 h. The dried aluminum foil was then pressed on a roller press and subsequently sliced using a punching machine to obtain cathode sheets with a diameter of 12 mm and an areal loading of 130–150 g / m². 2 .
[0109] (5) Battery manufacturing
[0110] In an argon-filled glove box (H2O < 1 ppm, O2 < 1 ppm), a battery was assembled using the positive electrode sheet prepared in step (4) as the positive electrode, a lithium metal sheet as the negative electrode, and 1 mol / L LiPF6 / EC:DMC (EC represents ethylene carbonate, DMC represents dimethyl carbonate, and the mass ratio of EC to DMC is 1:1) as the electrolyte. The battery's charge-discharge performance was tested, with a voltage range of 2.8–4.45 V and a charge-discharge current density of 0.1 C.
[0111] Example 2
[0112] The difference between Example 2 and Example 1 is as follows:
[0113] In step (2), the fluorine-containing ternary cathode material precursor prepared in step (1), along with lanthanum chloride and molybdenum chloride, are mixed uniformly in a solvent to prepare a fluorine-containing ternary cathode material precursor Ni coated with an oxygen ion conductor precursor. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 @La2Mo2(OH)9. In this mixture, which consists of a ternary cathode material precursor containing fluorine, lanthanum chloride, and molybdenum chloride, the total mass percentage of lanthanum chloride and molybdenum chloride is 1000 ppm, and the molar ratio of lanthanum chloride to molybdenum chloride is 1:1.
[0114] In step (3), a ternary cathode material LiNi containing fluorine element coated with an oxygen ion conductor is obtained. 0.6 Co 0.1 Mn0.3O 1.995 F 0.01 @La2Mo2O9.
[0115] Example 3
[0116] The difference between Example 3 and Example 1 is that:
[0117] In step (2), the fluorine-containing ternary cathode material precursor prepared in step (1), along with lanthanum chloride and molybdenum chloride, are mixed uniformly in a solvent to prepare a fluorine-containing ternary cathode material precursor Ni coated with an oxygen ion conductor precursor. 0.6 Co 0.1 Mn 0.3 (OH) 1.99 F 0.01 @La2Mo2(OH)9. In this mixture, which consists of a ternary cathode material precursor containing fluorine, lanthanum chloride, and molybdenum chloride, the total mass percentage of lanthanum chloride and molybdenum chloride is 4000 ppm, and the molar ratio of lanthanum chloride to molybdenum chloride is 1:1.
[0118] In step (3), a ternary cathode material LiNi containing fluorine element coated with an oxygen ion conductor is obtained. 0.6 Co 0.1 Mn0.3O 1.995 F 0.01 @La2Mo2O9.
[0119] Comparative Example 1
[0120] The difference between Comparative Example 1 and Example 1 is that:
[0121] No step (2);
[0122] In step (3), the ternary cathode material precursor containing fluorine element prepared in step (1) and lithium carbonate are added to a ball mill to prepare the ternary cathode material LiNi containing fluorine element. 0.6 Co 0.1 Mn 0.3 O 1.995 F 0.01 .
[0123] In step (4), the ternary cathode material containing fluorine element prepared in step (3), conductive carbon black, and binder are ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2.
[0124] Comparative Example 2
[0125] The difference between Comparative Example 2 and Example 1 is as follows:
[0126] In step (1), nickel sulfate, cobalt sulfate, and manganese sulfate are dissolved in a solvent at a molar ratio of 6:1:3 and mixed evenly to obtain a ternary metal solution, thus preparing the ternary cathode material precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH)2.
[0127] In step (2), the ternary cathode material precursor prepared in step (1), lanthanum chloride, and niobium chloride are mixed evenly in a solvent to obtain a ternary cathode material precursor Ni coated with an oxygen ion conductor precursor. 0.6 Co 0.1 Mn 0.3 (OH)2@La2Nb2(OH)9.
[0128] In step (3), the ternary cathode material precursor coated with the oxygen ion conductor precursor prepared in step (2) and lithium carbonate are added to a ball mill to prepare the oxygen ion conductor coated ternary cathode material LiNi. 0.6 Co 0.1 Mn 0.3 O2@La2Nb2O9.
[0129] In step (4), the ternary cathode material coated with oxygen ion conductor prepared in step (3), conductive carbon black, and binder are ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2.
[0130] Comparative Example 3
[0131] The difference between Comparative Example 3 and Example 1 is as follows:
[0132] In step (1), nickel sulfate, cobalt sulfate, and manganese sulfate are dissolved in a solvent at a molar ratio of 6:1:3 to prepare the ternary cathode material precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH)2.
[0133] No step (2).
[0134] In step (3), the ternary cathode material precursor prepared in step (1) and lithium carbonate are added to a ball mill to prepare the ternary cathode material LiNi. 0.6 Co 0.1 Mn 0.3 O2.
[0135] In step (4), the ternary cathode material, conductive carbon black, and binder prepared in step (3) are ground into a slurry with an appropriate amount of NMP solvent at a mass ratio of 95:3:2.
[0136] Test method:
[0137] (1) Battery first discharge specific capacity test: Charge the battery to 4.3V with a constant current of 0.1C, then charge it to 4.3V with a constant voltage, and then discharge it to 3.0V with a constant current of 0.1C to test the battery first discharge specific capacity.
[0138] (2) Battery cycle performance test: The initial discharge capacity C1 was measured after one charge-discharge cycle at a temperature of 25℃, 3V~4.3V, and 1C current density. The discharge capacity C2 was obtained after 100 cycles at 1C current density. The capacity retention rate after 100 cycles was calculated as C2 / C1.
[0139] (3) The amount of transition metal ions dissolved from the lithium metal anode surface of the batteries in the examples and comparative examples after 100 cycles was determined: The content of transition metals dissolved from the lithium metal anode after cycling was determined by inductively coupled plasma (ICP-OES) technology. Sample preparation method: The battery after 100 cycles was disassembled, the lithium metal anode was removed, and it was dissolved in 10 ml of frozen distilled water. After the solution was filtered through a 0.45 μm aqueous filter membrane, the ICP-OES test sample was obtained. The prepared sample was placed in an ICP-OES instrument to measure the content of nickel, cobalt, and manganese ions remaining on the anode surface, in ppm.
[0140] (4) Thermal Decomposition Temperature Test: Before the test, a differential scanning calorimeter (DSC) needs to be prepared and ensured to be in good working order. A dry and pure positive electrode sample is also required, obtained by dissection after constant current and constant voltage charging at 0.1C to 4.45V cutoff. During the test, 5 mg of positive electrode powder is placed in the DSC, with a heating rate of 10℃ / min, a heating range of 25–450℃, and a N2 protective atmosphere. The test program is then started. As the temperature increases, the DSC records the difference in heat flow rate between the sample and the reference material and plots a differential scanning calorimetry (DSC) curve. By analyzing the DSC curve, the heat released by the sample during thermal decomposition is determined.
[0141] The batteries prepared through the above embodiments and comparative examples were subjected to 0.1C first discharge specific capacity test, 0.1C 100-cycle performance test, transition metal dissolution test and thermal decomposition temperature test. The test results are shown in Table 1.
[0142] Table 1
[0143]
[0144] As can be seen from the test results in Table 1, the capacity retention rate of Examples 1-3 after 100 cycles all exceeded 92.5%, which was significantly better than the 89.0-89.8% of Comparative Examples 1-3, demonstrating the effect of the oxygen ion conductor coating layer on improving the cycle stability of the ternary cathode material. In Example 3, although the battery discharge specific capacity decreased slightly (200.9 mAh / g) when the coating layer was increased to 4000 ppm, the battery capacity retention rate further improved to 93.5%, while the amount of transition metal dissolution decreased to a minimum of 90 ppm. This indicates that a thicker oxygen ion conductor coating layer can more effectively suppress the side reactions at the electrode-electrolyte interface.
[0145] Furthermore, the transition metal leaching amounts in Examples 1-3 (90-124 ppm) were significantly lower than those in Comparative Examples 1-3 (201-222 ppm). This is because the composite oxide structure formed by the multivalent metal elements in the oxygen ion conductor coating layer and the transition metal effectively blocks the electrolyte from corroding the cathode material. Simultaneously, the doping of fluorine further stabilized the crystal structure and reduced the leaching of high-valence transition metal ions. This dual protection mechanism was further verified in high-temperature performance tests: the thermal decomposition temperatures of Examples 1-3 (256-259 °C) were 3-6 °C higher than those of the comparative examples (250-253 °C), indicating a significant enhancement in the thermal stability of the material. The lanthanum-molybdenum-based coating (Examples 2-3) exhibited superior performance compared to the lanthanum-niobium-based coating (Example 1). Although the initial capacities of both were similar, the lanthanum-molybdenum-coated sample showed advantages in cycle retention (93.2% vs 92.5%) and transition metal dissolution inhibition (101 ppm vs 124 ppm), which may be related to Mo. 6+ It is related to higher chemical stability and better oxygen ion conduction ability.
[0146] Furthermore, the synergistic effect of fluorine doping and oxygen ion conductor coating is particularly evident in the comparative analysis: the performance improvement effects of Comparative Example 1 (fluorine doping only) and Comparative Example 2 (coating only) are limited, while Examples 1-3 achieve comprehensive improvement in all indicators. This synergistic effect is mainly reflected in three aspects: First, fluorine doping stabilizes the bulk structure of the ternary cathode material, reduces lattice distortion during battery cycling, and provides a more stable core structure for the oxygen ion conductor coating layer; second, the oxygen ion conductor coating layer suppresses interfacial side reactions, protecting the structural stability advantage brought by fluorine doping; finally, fluorine may partially enter the lattice of the oxygen ion conductor coating layer, optimizing the ion conduction performance of the oxygen ion conductor. This multi-level synergistic effect enables the batteries corresponding to the examples to achieve simultaneous improvement in cycle life and safety performance while maintaining high capacity.
[0147] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.
[0148] The above provides a detailed description of the cathode material, preparation method, battery, and electrical device provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A positive electrode material, characterized in that, include: The core comprises a ternary cathode material containing fluorine. A shell layer disposed on the surface of the core, the shell layer comprising an oxygen ion conductor.
2. The cathode material according to claim 1, characterized in that, The oxygen ion conductor is a multivalent metal-based transition metal oxide, and the multivalent metal includes at least one of La, Zr, Ce, and Bi.
3. The cathode material according to any one of claims 1-2, characterized in that, The chemical formula of the oxygen ion conductor is: La2M2O9, where M represents at least one of W, V, Nb, Ta, and Mo.
4. The cathode material according to any one of claims 1-3, characterized in that, The chemical formula of the kernel is: LiNi a Co b Mn c O 2-0.5d F d , where a+b+c=1, 0.5<a<0.8, 0<d≤0.
02.
5. The cathode material according to any one of claims 1-4, characterized in that, In the positive electrode material, the mass ratio of the oxygen ion conductor to the fluorine element is (0.25~1):
1.
6. The cathode material according to any one of claims 1-5, characterized in that, In the positive electrode material, the content of the oxygen ion conductor is 1000-3000 ppm.
7. A method for preparing a positive electrode material, characterized in that, The method includes: A ternary cathode material precursor containing fluorine was prepared by mixing a nickel source, a cobalt source, a manganese source, a fluorine source, a precipitant solution, and a complexing agent solution. The ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor are mixed to prepare a ternary cathode material precursor containing fluorine coated with the oxygen ion conductor precursor. The fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor is mixed with lithium salt and sintered to obtain the fluorine-containing ternary cathode material coated with the oxygen ion conductor.
8. The method for preparing the cathode material as described in claim 7, characterized in that, The molar ratio of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source is a:b:c, where a+b+c=1 and 0.5<a<0.
8.
9. The method for preparing the cathode material according to any one of claims 7-8, characterized in that, The sum of the amounts of nickel in the nickel source, cobalt in the cobalt source, and manganese in the manganese source, and the amount of fluorine in the fluorine source, is in the ratio of 1:(0.0008 to 0.0012).
10. The method for preparing the cathode material according to any one of claims 7-9, characterized in that, In the mixture composed of the ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor, the content of the oxygen ion conductor precursor is 1000-3000 ppm. And / or, the oxygen ion conductor precursor comprises a multivalent metal salt and a transition metal salt, wherein the molar ratio of the multivalent metal element in the multivalent metal salt to the transition metal element in the transition metal salt is 1:(1.01~1.02); And / or, the mass ratio of the oxygen ion conductor precursor to the fluorine element in the fluorine source is (0.25~1):
1.
11. The method for preparing the cathode material as described in claim 10, characterized in that, The multivalent metal salt is at least one of lanthanum salt, zirconium salt, cerium salt, and bismuth salt.
12. The method for preparing the cathode material as described in claim 10 or 11, characterized in that, The transition metal element is at least one of W, V, Nb, Ta, and Mo.
13. The method for preparing the cathode material as described in claim 12, characterized in that, When the transition metal element is W, the transition metal salt is at least one of tungsten chloride, ammonium tungstate, and sodium tungstate; When the transition metal element is V, the transition metal salt is at least one of ammonium metavanadate and vanadium chloride; When the transition metal element is Nb, the transition metal salt is at least one of niobium oxalate, niobium chloride, and niobium sulfate; When the transition metal element is Ta, the transition metal salt is at least one of tantalum oxalate, tantalum chloride, and tantalum sulfate; When the transition metal element is Mo, the transition metal salt is at least one of ammonium molybdate, sodium molybdate, and potassium molybdate.
14. The method for preparing the cathode material as described in claim 7, characterized in that, The molar ratio of the fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor to the lithium element in the lithium salt is 1:(0.50~0.52).
15. The method for preparing the cathode material according to any one of claims 7-9, characterized in that, A ternary cathode material precursor containing fluorine is prepared by mixing a nickel source, a cobalt source, a manganese source, a fluorine source, a precipitant solution, and a complexing agent solution, further comprising: Nickel source, cobalt source, manganese source and fluorine source are mixed evenly in solvent, precipitant and complexing agent are added to make the pH of the solution 11-12, and the reaction is carried out by stirring in a water bath at 60-70℃ for 1-2 hours. After aging in a water bath at 60℃~70℃ for 12~13h, the precipitate is obtained by vacuum filtration. The precipitate is then washed and dried to obtain the ternary cathode material precursor containing fluorine.
16. The method for preparing the cathode material according to any one of claims 7, 10-13, characterized in that, The ternary cathode material precursor containing fluorine and the oxygen ion conductor precursor are mixed to prepare a ternary cathode material precursor containing fluorine coated with the oxygen ion conductor precursor, further comprising: The fluorine-containing ternary cathode material precursor and the oxygen ion conductor precursor are mixed evenly in a solvent and subjected to a hydrothermal reaction at 100–200°C for 8–12 h to obtain a fluorine-containing ternary cathode material precursor coated with an oxygen ion conductor precursor.
17. The method for preparing the cathode material as described in claim 7 or 14, characterized in that, The fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor is mixed with a lithium salt and sintered to obtain an oxygen ion conductor-coated fluorine-containing ternary cathode material, further comprising: The fluorine-containing ternary cathode material precursor coated with the oxygen ion conductor precursor and lithium salt are ball-milled and mixed, and then sintered under a protective atmosphere to obtain the fluorine-containing ternary cathode material coated with the oxygen ion conductor. The sintering temperature is 650-750℃ and the sintering time is 9-11h.
18. A battery, characterized in that, It includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the positive electrode material as described in any one of claims 1-6.
19. An electrical appliance, characterized in that, Includes the battery as described in claim 18, wherein the battery serves as the power supply for the electrical device.